Gerakan Femen di Ukraina dalam Kritik Posmodern Feminisme Terhadap Posfeminisme - Dias Pabyantara (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2015)
This paper argues, posfeminist claims in post-1990 about the absence of oppression of women by patriarchal structures is not entirely true. They are still there. One indication is the emergence of a topless movement called Femen. in Ukraine. They protest against three things: dictatorship, religious institutions and the sex industry. The emergence of the Ukrainian Femen at least supported by two things, domestic and international. Domestic factors consist of democratization and Barbie lifestyle emerging in Ukraine and international factors that include the globalization of information and the ratification of the International Convention CEDAW. These factors support the assumption about the emergence of Femen as postmodern, in a quadrant of the second wave of feminism. This movement has been falsely interpreted as the existence of oppression of female identity in the midst of patriarchal structure.